2017
DOI: 10.1159/000470911
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine/Citrate Lock Therapy for Primary Prevention of Catheter-Related Infections in Cancer Patients: Results of a Prospective, Randomized, Phase IV<b> </b>Trial (ATAPAC)

Abstract: Background: Totally implantable venous access port (TIVAP)-related infections (RIs) remain a serious health problem in cancer patients receiving an intravenous (i.v.) therapy. Patients and Methods: The ATAPAC study was a prospective, randomized, monocentric, phase IV trial evaluating the efficacy of taurolidine lock solution versus standard saline solution for primary TIVAP-RI prevention in nonhematological cancer patients receiving i.v. chemotherapy. The primary endpoint was the TIVAP-RI incidence rate. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
15
0
5
Order By: Relevance
“…Cationic chelator-based solutions combined with antiinfectious agents not used for parenteral administration have been successfully used for preventing long-term catheter infections. In contrast, lock solutions with citrate alone, taurolidine citrate, or concentrated ethanol have yielded conflicting results on their efficacy for CRBSI prevention or maintaining catheter patency [97][98][99][100].…”
Section: Catheter Lock For Preventing Thrombotic and Infectious Complmentioning
confidence: 99%
“…Cationic chelator-based solutions combined with antiinfectious agents not used for parenteral administration have been successfully used for preventing long-term catheter infections. In contrast, lock solutions with citrate alone, taurolidine citrate, or concentrated ethanol have yielded conflicting results on their efficacy for CRBSI prevention or maintaining catheter patency [97][98][99][100].…”
Section: Catheter Lock For Preventing Thrombotic and Infectious Complmentioning
confidence: 99%
“…On the contrary, a third study of paediatric patients with totally implantable venous access ports showed no beneficial effect [ 27 ]. Likewise, in a recent prospective, randomised, phase IV trial, taurolidine-citrate did not show a significant reduction in the risk of infection when used in adult patients with non-haematological cancer [ 31 ]. These studies have important limitations due to the lack of data on adult and/or high-risk neutropenic patients, the type of catheters studied (tunnelled or ports), and the lack of information regarding the intervention (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not an antibiotic, it has a wide array of antimicrobial activity against a broad spectrum of microorganisms, including Gram-positive bacteria, Gram-negative bacteria, and fungi. Taurolidine-citrate was found to be effective in two [ 28 , 29 ] of the three studies involving paediatric patients with cancer, reducing CRBSI rates compared with heparin solutions, but it did not offer any benefit when used in the single adult study performed in patients with non-haematological cancer who had totally implantable venous access ports implanted [ 31 ]. The scarce and heterogeneous data obtained from these studies do not draw any solid conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in TIVAPs implantation, we use the basilic vein, subclavian vein, external jugular vein, or the internal jugular vein (IJV) as puncture sites. Since some patients with breast cancer may receive ipsilateral radiation treatment, the veins and chest wall of the contralateral side are the suitable choices for TIVAP implantation . From January 2013, the TIVAP implantation with IJV or subclavian vein as puncture site has been launched in our department.…”
Section: Comparison Of Achievement Ratio and Operation Duration By DImentioning
confidence: 99%
“…Since some patients with breast cancer may receive ipsilateral radiation treatment, the veins and chest wall of the contralateral side are the suitable choices for TIVAP implantation. 5 From January 2013, the TIVAP implantation with IJV or subclavian vein as puncture site has been launched in our department. The chamber of the port has been placed into the chest wall of the healthy side, and the catheter has been introduced to the superior vena cava (SVC).…”
mentioning
confidence: 99%